The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1517-83822010000400022
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and biocides inactivation of Salmonella on stainless steel and polyethylene

Abstract: The adhesion of Salmonella (S.) strains to stainless steel and polyethylene and their inactivation by biocides used in food industry was investigated. Coupons of stainless steel and polyethylene were immersed in bacterial suspensions of S. Enteritidis, S. Typhimurium, and S. Bredeney during 15, 30, and 60 minutes, and submitted to different concentrations of peracetic acid (PAA), sodium hypochlorite (NaOCl), and quaternary ammonium (Quat) sanitizers. Hydrophobicity of the surfaces was evaluated by contact angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 27 publications
3
13
1
Order By: Relevance
“…Thus, for TSB with and without compounds, important differences in biofilm formation ability were observed between groups of cells (nonadapted or adapted to TSP, SNI, or SHY), even though no substantial differences in bacterial concentrations were found. These results agree with findings from other authors, who found that the number of attached cells remained constant over the period of incubation (31,32). It has been suggested that after a few hours of incubation, the surface reaches a saturation level where larger numbers of planktonic cells do not entail larger numbers of attached cells (7).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, for TSB with and without compounds, important differences in biofilm formation ability were observed between groups of cells (nonadapted or adapted to TSP, SNI, or SHY), even though no substantial differences in bacterial concentrations were found. These results agree with findings from other authors, who found that the number of attached cells remained constant over the period of incubation (31,32). It has been suggested that after a few hours of incubation, the surface reaches a saturation level where larger numbers of planktonic cells do not entail larger numbers of attached cells (7).…”
Section: Discussionsupporting
confidence: 92%
“…Malheiros et al (20) also found that Salmonella Enteritidis SE86 had a greater capacity for acid adaptation and thermal resistance than did other Salmonella serovars after exposure to sublethal pH. Tondo et al (36) found that Salmonella Enteritidis SE86 was more resistant to sodium hypochlorite than were other Salmonella serovars; however, in our study resistance of Salmonella Enteritidis SE86 to sodium hypochlorite was similar to that of other Salmonella Enteritidis serovars from other countries. Several researchers have reported very low genetic diversity among Salmonella Enteritidis strains (8,19).…”
Section: Results a N D Discussioncontrasting
confidence: 56%
“…The applied methodology is an adaptation from the literature Tondo et al 2010). Initially, the yeasts were grown in Sabouraud agar for 24 h at 37°C.…”
Section: Biofilm Formation Assay On Tracheal Catheter Materialsmentioning
confidence: 99%